Cascaded LC‐AC transformer unidirectional DC/DC converter with high stepping ratio. Issue 9 (21st May 2018) - Li, Mengbo; Xiang, Wang; Yao, Liangzhong; Xie, Zhujun; Lin, Weixing; Wen, Jinyu
Abstract : This paper proposes a unidirectional DC/DC converter termed LCT DC/DC, which has a high stepping ratio and is suitable for integrating renewable energy sources. The LCT DC/DC converter consists of four power modules, and each of them is composed of a voltage source converter (VSC), an inductor−capacitor circuit, an AC transformer, and a diode rectifier bridge. By means of the two‐stage voltage boost, a step‐up ratio as high as 40 is achieved. The topology, operating principle, and design procedure of the LCT DC/DC are elaborated. Then, the active power control strategy and power loss estimation are studied. Finally, the technical feasibility of the proposed topology is validated by simulations in PSCAD/EMTDC. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.